2021
DOI: 10.1186/s12985-021-01676-z
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, characteristics, and distribution of HPV genotypes in women from Zhejiang Province, 2016–2020

Abstract: Objective To evaluate and understand the prevalence of HPV genotypes and characteristics of female populations in specific areas and the relationship with cervical lesions, which can effectively guide cervical cancer screening and formulate HPV vaccine prevention strategies. Methods A total of 77,443 women who visited gynecological clinics and underwent health examinations in the Second Affiliated Hospital of Zhejiang University School of Medicine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
17
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 42 publications
14
17
6
Order By: Relevance
“…Similarly, different HPV-genotypes have different clinical implications. Study shows that HPV 52 is the most common type in CIN II across all age categories [44], and has the highest preponderance as indicated in another study conducted in Zhejiang Province [45]. HPV 51, 52, and 31 are also more common in precancerous lesions than in invasive cervical cancer, despite the fact that HPV 16, 18, and 45 are more frequent in invasive cervical cancer than in any other grades of cervical malignancy [46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, different HPV-genotypes have different clinical implications. Study shows that HPV 52 is the most common type in CIN II across all age categories [44], and has the highest preponderance as indicated in another study conducted in Zhejiang Province [45]. HPV 51, 52, and 31 are also more common in precancerous lesions than in invasive cervical cancer, despite the fact that HPV 16, 18, and 45 are more frequent in invasive cervical cancer than in any other grades of cervical malignancy [46].…”
Section: Discussionmentioning
confidence: 99%
“…According to a recent GLOBOCAN database, out of the infection-attributable cancer cases diagnosed worldwide, human papillomaviruses (HPV) caused about 31.1%, second to Helicobacter pylori (36.3%) [1]. HPV is the most common cause of cervical cancer, especially by high-risk HPV (hrHPV) genotypes such as HPVs 16,18,31,33,35,39,45,51,52,56,58,59, 66, and 68, according to the World Health Organization (WHO); [2]. Also, hrHPVs are the most important risk factors present in 99.7% of the invasive cervical cancer, particularly among the young women [3].…”
Section: Introductionmentioning
confidence: 99%
“…Our results have confirmed that a high HPV 51 prevalence exists in unvaccinated women aged 20–22 in Wales. A high proportion of HPV 51 has recently been seen in several prevalence studies undertaken in Scotland [ 22 , 23 , 24 ] and small studies of both HIV positive [ 25 ] and negative women in Sao Paulo, Brazil [ 26 ], in addition to studies in China [ 27 , 28 ], Iran [ 29 ] and Hungary [ 30 ]. However, in global meta-analyses of women with both cancerous and normal cytology, undertaken in 2011 and 2010, respectively, HPV 51 did not emerge as a highly prevalent genotype [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…A total of 40,613 women who underwent HPV-based screening from the physical examination center, gynecology clinic, and reproductive gynecology clinic of the First People's Hospital of Yunnan Province were included from January 2020 to December 2021. The inclusion criteria were as follows: (1) was physically and mentally competent; (2) was a history of sexual activity at any age; (3) was willing to undergo cervical HPV screening and provided agreement to participate in the present study; (4) had not had sexual intercourse, nor used vaginal drugs in the previous 48 h ( 11 ). The exclusion criteria were as follows: (1) patients with other infections or autoimmune diseases; (2) pregnant women; (3) patients who had undergone immunosuppressive therapy ( 11 ).…”
Section: Methodsmentioning
confidence: 99%
“…The inclusion criteria were as follows: (1) was physically and mentally competent; (2) was a history of sexual activity at any age; (3) was willing to undergo cervical HPV screening and provided agreement to participate in the present study; (4) had not had sexual intercourse, nor used vaginal drugs in the previous 48 h ( 11 ). The exclusion criteria were as follows: (1) patients with other infections or autoimmune diseases; (2) pregnant women; (3) patients who had undergone immunosuppressive therapy ( 11 ). This research was approved by the Institutional Review Board of the First People's Hospital of Yunnan Province, and carried out strictly in accordance with the Declaration of Helsinki, maintaining the confidentiality and anonymity.…”
Section: Methodsmentioning
confidence: 99%